To Develop RP-HPLC Method to Estimate Glimperide in Bulk Dosage Forms - Abdul Ajeez A; T Madhavi Latha; Dr.B.Swarupa; N Audinarayana; Dr.D Jothieswari (Asian Journal of Pharmaceutical Research and Development, 2025)
The present work is aimed to develop a new, simple, fast, rapid, accurate, efficient and reproducible RP-HPLC method for the simultaneous analysis of Glimperide. Literature review reveals that there is no analytical method reported for the analysis of Glimperide by simultaneous estimation by RP-HPLC. Spectrophotometer, HPLC and HPTLC are the reported analytical methods for compounds either individually or in combination with other dosage form. The solutions were chromatographed at a constant flow rate of 1ml/min and Injection volume 20ml, the run time 10min, the linearity range was found to lie from 20µg/ml to 100µg/ml of Glimepride. The correlation coefficient obtained was 0.999 which is in the acceptance limit. The % RSD values of Glimepride are found to be 0.11 and 0.42 indicating less than 2% precision of the method and Intermediate precision for Glimepride found to be 1.09 and 0.45. The percentage recovery varies from 98-102% of Glimperide found to be 99.06% and 99.96. LOD and LOQ were found to be within limit. The results obtained on the validation parameters met ICH and USP requirements. It inferred the method found to be simple, accurate, precise and linear. The method was found to be having suitable application in routine laboratory analysis with high degree of accuracy and precision.